DIGITALIZATION OF THE TRAVEL INDUSTRY - STATISTICS & FACTS: AN EXAMINATION OF UZBEKISTAN - Azimov Ulugbek; Tadjieva Sayyorakhon Uralovna; Suzanna Lamria Siregar (Galaxy International Interdisciplinary Research Journal, 2022)
Until two decades, virtual business had been seen a lot of across utmost diligence worldwide. business and trip trade is not any elision, with the event of the online business request and raising consumer need for virtual business services. on- line| the web| the net? trip request includes enterprises like on-line trip agencies (OTAs) – which allow excursionists to bespeak trip services autonomously on- ine – and trip review websites. Meanwhile, guests are trying to search out further digital gests once traveling. These can embody opinions like virtual tenures of a asked destination or accommodation, inversely as mobile integration results, like mistreatment associate app to search out new tourer lodestones or appearance to a chamber. As computable by Statista’s Digital Market Outlook, the worldwide profit of mobile apps inside the trip section rose by thirty pool ball in 2021 over the former time, amounting to 296 million U.S. dollars. The coronavirus (COVID- 19) epidemic could in addition play a crucial part in quick the medical care of this sector, with social distancing and hygiene problems making guests bay to use digital rather than in- person services. throughout this respect, a September 2021 study set up that roughly four in ten surveyed trippers worldwide indicated contactless mobile payments among the foremost technologies to increase trip confidence.